ROMEO AND JULIET: A CRITICAL ANALYSIS OF SHAKESPEARE’S USE OF LANGUAGE - Hafiz Haqnawaz; Tanweer Ahmed; Mohammad Ilyas (International Journal of Contemporary Issues in Social Sciences, 2024)
The study intends to examine Shakespearean language in Romeo and Juliet by claiming that the author’s understanding was deep to an extent that he was able to differentiate socially high and low status characters through the expression of their words. The concept of language has been represented as a main tool for the manifestation of any culture, society and even of human mind and nature. This is language which describes a human being whether high or low in status, the examination of a character, society and a whole nation is what can be consider as a combination of language. This research paper clearly demonstrates the nature of language in Shakespeare’s Romeo and Juliet and discusses to what extent the language in the play clarifies a reader mentally that a character speaking whether belongs to a high class family or a low family. The paper is qualitative by nature and employs social semiotics for the critical analysis of characters’ speeches. This signifies characters’ discourses clearly defining their nature and understanding towards the society. The main focus in this paper is on the dialogues of elite families which either refer to their social status in the society or their highness in the play. That is why, the recommendation for further studies resonates the concept of low class families’ language which is also another fact for the representation of their lives and status in the society. The present study determines language as an upended portion in Shakespearean plays.